Impact of Ir modification on the durability of FeNC catalysts under start-up and shutdown cycle conditions. Issue 11 (29th October 2021) - Prössl, Carolin; Kübler, Markus; Paul, Stephen; Ni, Lingmei; Kinkelin, Simon-Johannes; Heppe, Nils; Eberhardt, Klaus; Geppert, Christopher; Jaegermann, Wolfram; Stark, Robert W.; Bron, Michael; Kramm, Ulrike I.
Abstract : Ir modification of FeNC catalysts improves the durability of the catalysts, but causes electronic changes that are disadvantageous for the activity. Abstract : A common problem associated with FeNC catalysts is their poor stability dominated by the carbon oxidation reaction (COR). In this work, the feasibility of stabilizing FeNC catalysts with small quantities of Ir was explored. With iridium being present, instead of COR the oxygen evolution reaction should be favored. The impact on structure and morphology was investigated by 57 Fe Mössbauer spectroscopy, X-ray photoelectron spectroscopy, Raman spectroscopy and transmission electron microscopy. The catalytic activity and durability for the oxygen reduction reaction was evaluated by rotating ring disc electrode experiments and accelerated stress tests mimicking the start-up and shutdown cycle (SSC) conditions, respectively. For selected samples the stability was analysed for SSCs in proton exchange membrane fuel cells. Moreover, the faradaic efficiency towards oxygen evolution reaction vs. COR was determined and the resistance towards COR analysed by in situ Raman spectroscopy. The results indicate indeed a suppression of the COR; however, specifically for fuel cell applications, further optimization is necessary.